Chitons (Mollusca: Polyplacophora) on manganese nodules from the Clarion-Clipperton Zone and other regions - Sirenko, Boris I. (Zootaxa, 2026)
Two species of chitons Belknapchiton macleani (Sirenko, 2015) and Carinichiton chiversi (Ferreira, 1981) comb. nov. were found on manganese nodules in the Clarion-Clipperton Zone. For the latter species, a new genus Carinichiton gen. nov. is proposed. Features unique to this genus include aspects of the tegmentum sculpture, slits of insertion plates, and radular teeth. Besides the type locality, Carinichiton chiversi has been found in west of Oregon State, west of New Caledonia, and in the Drake Passage. Scanning electron microscope studies have provided new data on the sculpture of the valves, composition and shape of the perinotum spicules and the shape of radular teeth. These new observations provide an opportunity to discuss the likely feeding mode of chitons on manganese nodules. A series of samples with variable sizes also offers new insights to age variability of the valve keel as a feature.